2019
DOI: 10.1002/humu.23861
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of blind predictions of the clinical significance of BRCA1 and BRCA2 variants

Abstract: Testing for variation in BRCA1 and BRCA2 (commonly referred to as BRCA1/2), has emerged as a standard clinical practice and is helping countless women better understand and manage their heritable risk of breast and ovarian cancer. Yet the increased rate of BRCA1/2 testing has led to an increasing number of Variants of Uncertain Significance (VUS), and the rate of VUS discovery currently outpaces the rate of clinical variant interpretation. Computational prediction is a key component of the variant interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 41 publications
1
31
0
1
Order By: Relevance
“…Following this line of thought, it will be important that estimates of prior probability based on bioinformatic predictions are re‐estimated using updated datasets that reflect changed variant pools, and altered patient ascertainment in the era of multigene panel testing. Results arising from the CAGI 5 experiment (Cline et al, ), and other similar studies, are likely to inform development of such bioinformatic methods.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Following this line of thought, it will be important that estimates of prior probability based on bioinformatic predictions are re‐estimated using updated datasets that reflect changed variant pools, and altered patient ascertainment in the era of multigene panel testing. Results arising from the CAGI 5 experiment (Cline et al, ), and other similar studies, are likely to inform development of such bioinformatic methods.…”
Section: Resultsmentioning
confidence: 94%
“…A prepublication iteration of the classification dataset was used as a reference set for the Critical Assessment of Genome Interpretation (CAGI) 5 experiment, results from which are presented in this same Journal issue (Cline et al, ). Comparison of various different prediction methods from six different teams highlighted that prediction of mRNA splicing is an important inclusion in variant interpretation algorithms, and also indicated that variant interpretation may be improved by incorporating amino acid accessibility as a component of bioinformatic prediction of variant effect.…”
Section: Resultsmentioning
confidence: 99%
“…We next compare three types of machine learning models, as previously summarized in Table , for the task of pathogenicity prediction: MLR , a representative of multiclass classification used by other participants in the Challenge (Cline et al, ); CLM , a representative of multiclass classification that considers the order among classes (ordinal regression); and our three WSR models that directly predict the probability of pathogenicity from training pathogenicity classes using designed loss functions, summarized and compared in Table . Due to the lack of ground‐truth PoP values, we were only able to assess classification performances.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the mutation was not found to destabilize BRCA1 (Figure S2). Interestingly, the top‐performing LEAP team found that splicing information, such as the distance to the nearest splice site, was also important for correctly annotating the clinical significance of some variants (Cline et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation